Effect of Fodder Tree Species with Condensed Tannin Contents on Methane Production - Ernestina Gutiérrez Vázquez; Leonardo Hernández Medina; Liliana Márquez Benavides; Aureliano Juárez Caratachea; Guillermo Salas Razo; Armin Javier Ayala Burgos; Ruy Ortiz Rodríguez (Asian-Australasian Journal of Animal Sciences, 2016)
The objective was to evaluate the effect of fodder tree species (FTS) with condensed tannin contents: Cordia elaeagnoides, Platymiscium lasiocarpum, Vitex mollis, and Haematoxylon brasiletto, on in vitro methane (CH4) production at 24 h post incubation. The analysis was performed using the in vitro gas production technique, with three levels of inclusion/species: 600, 800, and 1,000 mg and with 4 replicates/species/level of inclusion. The substrate was incubated at 39°C, and the gas and CH4 production were recorded at 4, 8, 12, and 24 h post incubation. The data collected was analyzed through Pearson correlation, polinomial regression and fixed effects models. There were negative correlations between FTS-total gas volume (r = −0.40; p<0.001); FTS-volume of CH4 produced (r = −0.40; p<0.001) and between the inclusion level-volume of CH4 produced (r = −0.20; p<0.001). As well as a positive correlation between hours post incubation-total gas volume (r = 0.42; p<0.001) and between hours post incubation-volume of CH4 produced (r = 0.48; p<0.001). The FTS: C. elaeagnoides, V. mollis, and H. brasiletto have potential, in the three inclusion levels analyzed, to reduce CH4 emission on in vitro trials (>32.7%), taking into account the total CH4 production at 24 h of the forage used as reference (Avena sativa). It’s suggested that C. elaeagnoides-according to its crude protein, neutral detergent fiber, and condensed tannins content- is the best alternative within the FTS analyzed, for feeding ruminants and for the control of CH4 emissions during the dry season.